2018
DOI: 10.3390/s18082488
|View full text |Cite
|
Sign up to set email alerts
|

Interval Fuzzy Model for Robust Aircraft IMU Sensors Fault Detection

Abstract: This paper proposes a data-based approach for a robust fault detection (FD) of the inertial measurement unit (IMU) sensors of an aircraft. Fuzzy interval models (FIMs) have been introduced for coping with the significant modeling uncertainties caused by poorly modeled aerodynamics. The proposed FIMs are used to compute robust prediction intervals for the measurements provided by the IMU sensors. Specifically, a nonlinear neural network (NN) model is used as central prediction of the sensor response while the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Therefore, an outlier can never be identified if it occurs in one of these measurements, but it can be detected. 1.00 0.98 0.93 ∆h 5 1.00 0.98 ∆h 6 1.00…”
Section: On the Probability Levels Of Iterative Outlier Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an outlier can never be identified if it occurs in one of these measurements, but it can be detected. 1.00 0.98 0.93 ∆h 5 1.00 0.98 ∆h 6 1.00…”
Section: On the Probability Levels Of Iterative Outlier Eliminationmentioning
confidence: 99%
“…In recent years, Outlier Detection has been increasingly applied in sensor data processing [1][2][3][4][5][6][7][8][9]. Despite the countless contributions made over the years, there is continuing research on the subject, mainly because there has been an increase in computational power.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Hardware Physics Redundancy (HPR) can significantly improve the reliability of IMU, it is necessary to pay due attention to the faults in IMU measurements. A significant number of serious accidents have happened due to IMU failures, such as the crashes of the Qantas F72 and Croatia Boeing 737-200 [29]. In addition, given that low-cost IMU sensors may be carried on UAVs for future UAM applications, such as passenger/cargo air transportation, the output of IMU must be monitored against the possible faults.…”
Section: Of 21mentioning
confidence: 99%
“…It was reported that LMI can be used for identification and estimation. LMI can be also used for model identification [20]. To calculate the fault estimation algorithm, additional design constraints were faced, which could not be solved with typical methods.…”
Section: Literature Surveymentioning
confidence: 99%